Implementation of the Design Thinking Method for Validation Of Business Ideas in Sea Fish Selling Business in Sijelling Village, Tellusiattinge District, Bone Regency - Rismang, Rismang; Niswaty, Risma; Wafiqah Wardah, Siti Syarifah (Pinisi Business Administration Review, 2024)
Implementation of the Design Thinking Method for Validating Business Ideas in Seafood Selling Businesses in Sijelling Village, Tellusiattinge District, Bone Regency. Thesis of the Faculty of Social Sciences and Law, Business Administration Study Program, Makassar State University. This study aims to find out how to implement the design thinking method to validate business ideas for selling marine fish. To achieve this goal, this study used a qualitative approach, this study took 6 (six) respondents, consisting of consumers and fish manufacturers. Data collection procedures used were in-depth interviews and documentation. The interview technique was carried out in a structured manner using design thinking interview guidelines. The results of this study indicate that the implementation of the design thinking method can create products according to user needs through the stages of empathize, define, ideate, prototyping, and testing. After carrying out several stages of design thinking, this research resulted in a prototype design in the form of a business model canvas (BMC). Business model creation can be run with the nine elements of the business model canvas. The nine elements are customer segment, value proposition, channel, customer relationship, revenue streams, key resources, key activities, key partners and cost structure.